MACROECONOMIC VARIABLES AFFECTING THE FISH TRADE BALANCE IN MALAYSIA (Journal of Economics and Sustainability, 2020)
The world demand for fish has been increasing. Malaysia has a high fish trade with other countries. However, Malaysia, which has been one of the main fish producers given its long coastlines, still experiences a fish trade deficit. The present study aims to explore the effect of macroeconomic factors on the Malaysian fish trade balance by implementing the Vector Error Correction Model (VECM) on the time series data from 1976 to 2016. The findings reveal that foreign income is positively correlated with the trade balance in both short-run and long-run. Nevertheless, trade openness, depreciation of exchange rate, and money supply show a negative effect on the trade balance for the long-run mainly. The incidents are mainly due to fish import dependence and a lack of capacity of exporting fish. To strengthen the trade balance, reducing fisheries products export duties and restricting imported fisheries products are highly recommended.Received 24 March 20. Revised 6 April 20. Accepted 19 April 20.